Distinct MicroRNA Profiles in the Perilymph and Serum of Patients With Menière's Disease - Shew, Matthew; Wichova, Helena; St. Peter, Madeleine; Warnecke, Athanasia; Staecker, Hinrich (Frontiers in Neurology, 2021)
Hypothesis: Menière’s disease microRNA (miRNA) profiles are unique and are reflected in the perilymph and serum of patients. Background: Development of effective biomarkers for Menière’s disease are needed. miRNAs are small RNA sequences that downregulate mRNA translation and play a significant role in a variety of disease states, ultimately making them a promising biomarker. miRNAs can be readily isolated from human inner ear perilymph and serum, and may exhibit disease-specific profiles. Methods: Perilymph sampling was performed in 10 patients undergoing surgery; 5 patients with Meniere’s disease and 5 patients with otosclerosis serving as controls. miRNAs were isolated from the serum of 5 patients with bilateral Menière’s disease and compared to 5 healthy age-matched controls. For evaluation of miRNAs an Agilent miRNA gene chip was used. Analysis of miRNA expression was carried out using Qlucore and Ingenuitey Pathway Analysis software. Promising miRNAs biomarkers were validated using qPCR. Results: In the perilymph of patients with Menière’s disease, we identified 16 differentially expressed miRNAs that are predicted to regulate over 220 different cochlear genes. Six miRNAs are postulated to regulate aquaporin expression and twelve miRNAs are postulated to regulate a variety of inflammatory and autoimmune pathways. When comparing perilymph with serum samples, miRNA 1299 and 1270 were differentially expressed in both the perilymph and serum of Ménière’s patients compared to controls. Further analysis using qPCR confirmed miRNA-1299 is downregulated over 3-fold in Meniere’s disease serum samples compared to controls. Conclusions: Patients with Ménière’s disease exhibit distinct miRNA expression profiles within both the perilymph and serum. The altered perilymph miRNAs identified can be linked to postulated Ménière’s disease pathways and may serve as biomarkers. miRNA-1299 was validated to be downregulated in both the serum and perilymph of Menière’s patients.